RASAN TUE: BUDAYA PERKAWINAN SUKU PASEMAH (Rasan Tue: Marriage Culture of Pasemah Tribe) - Wardani Wardani (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2021)
This study attempts to describe culture rasan tue marriage in the Padang Guci Bengkulu. The methodology used is a descriptive qualitative method anthropological approach. The research was conducted by observing directly the Pasemah tribe’s marriage culture in the Padang Guci Bengkulu. This study summarizes the phases of rasan tue marriage culture completely. The result shows that marriage with rasan tue culture is held for some reasons: (1) the boy and the girl have a kinship, despite far relative, (2) the boy and the girl are equally shy so that they do not have the courage to express their feelings and need parents’ help to communicate it, (3) both girl and boy have been adult and they have acquaintance with adult boy and girl, and (4) the boy and the girl have wealth so that it was necessary to make the agreement between the two parties by presenting both parents. It can be concluded that the procedure of marriage using rasan tue culture involves, among others: meminang (proposing), miare tunang, nolong tunang, tandang with tunang, ngalih panggilan, setting up marriage time, netak akhi malam, and holding the marriage (wedding) event.